A review of non-fullerene polymer solar cells: from device physics to morphology control. (26th February 2019) - Gurney, Robert S; Lidzey, David G; Wang, Tao
Abstract: The rise in power conversion efficiency of organic photovoltaic (OPV) devices over the last few years has been driven by the emergence of new organic semiconductors and the growing understanding of morphological control at both the molecular and aggregation scales. Non-fullerene OPVs adopting p-type conjugated polymers as the donor and n-type small molecules as the acceptor have exhibited steady progress, outperforming PCBM-based solar cells and reaching efficiencies of over 15% in 2019. This review starts with a refreshed discussion of charge separation, recombination, and V OC loss in non-fullerene OPVs, followed by a review of work undertaken to develop favorable molecular configurations required for high device performance. We summarize several key approaches that have been employed to tune the nanoscale morphology in non-fullerene photovoltaic blends, comparing them (where appropriate) to their PCBM-based counterparts. In particular, we discuss issues ranging from materials chemistry to solution processing and post-treatments, showing how this can lead to enhanced photovoltaic properties. Particular attention is given to the control of molecular configuration through solution processing, which can have a pronounced impact on the structure of the solid-state photoactive layer. Key challenges, including green solvent processing, stability and lifetime, burn-in, and thickness-dependence in non-fullerene OPVs are briefly discussed.